2008
DOI: 10.1021/es800702k
|View full text |Cite
|
Sign up to set email alerts
|

High Accumulation of Perfluorooctane Sulfonate (PFOS) in Marine Tucuxi Dolphins (Sotalia guianensis) from the Brazilian Coast

Abstract: Perfluorooctane sulfonate (PFOS) and other perfluoroalkyl compounds (PFCs) were measured in liver samples from 29 marine tucuxi dolphins from Rio de Janeiro state (RJ), Brazil. PFC measurement combined liquid chromatography and mass spectrometry, using a CapLC system connected to a Quadrupole-LIT mass spectrometer. PFOS was the only PFC detected and it was so in all samples. PFOS concentrations (ng · g -1 dw) of dolphins (n ) 23) from the highly contaminated Guanabara Bay (in RJ) varied between 43 and 2431 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 61 publications
2
29
0
2
Order By: Relevance
“…The concerns generated by the DRC contamination are amplified when it is taken into account that these cetaceans are exposed to other persistent bioaccumulative toxicants (PBTs) that have been shown to be endocrine disrupters, tumor promoters and immunosuppressors as well (Schecter et al, 2006;Simonyte et al, 2006;Sonne et al, 2006a;Whalen et al, 1999). The high exposure of cetaceans from Brazil to cadmium (Dorneles et al, 2007a(Dorneles et al, , 2007b, mercury (Lailson-Brito et al, 2012a), organochlorine pesticides (Lailson-Brito et al, 2011, 2010, 2012b, as well as to organotin (Dorneles et al, 2008b), perfluoroalkyl (Dorneles et al, 2008a) and organobrominated (Alonso et al, 2012;Dorneles et al, 2010) compounds has already been reported. Therefore, the possibility of synergistic effects among these PBTs should not be ruled out.…”
Section: A Serious Pcb Problemmentioning
confidence: 99%
“…The concerns generated by the DRC contamination are amplified when it is taken into account that these cetaceans are exposed to other persistent bioaccumulative toxicants (PBTs) that have been shown to be endocrine disrupters, tumor promoters and immunosuppressors as well (Schecter et al, 2006;Simonyte et al, 2006;Sonne et al, 2006a;Whalen et al, 1999). The high exposure of cetaceans from Brazil to cadmium (Dorneles et al, 2007a(Dorneles et al, , 2007b, mercury (Lailson-Brito et al, 2012a), organochlorine pesticides (Lailson-Brito et al, 2011, 2010, 2012b, as well as to organotin (Dorneles et al, 2008b), perfluoroalkyl (Dorneles et al, 2008a) and organobrominated (Alonso et al, 2012;Dorneles et al, 2010) compounds has already been reported. Therefore, the possibility of synergistic effects among these PBTs should not be ruled out.…”
Section: A Serious Pcb Problemmentioning
confidence: 99%
“…PFOSA was also reported in mammals as a metabolic product of N-EtFOSA, used as an insecticide, named Sulfluramid, for agricultural control of leaf-cutting ants in Brazil as well as for the domestic control of cockroaches and termites. [93][94][95] In mammals, PFOSA can rapidly be metabolised to PFOS. [93] Remarkably high PFOSA concentrations (in the same order as PFOS) were reported in liver of whales from the Canadian Arctic, from Iceland and the Faroe Islands and from Japan as well as in dolphins from Brazil (Table 1).…”
Section: Pfc Pattern In Marine Mammalsmentioning
confidence: 99%
“…[93][94][95] In mammals, PFOSA can rapidly be metabolised to PFOS. [93] Remarkably high PFOSA concentrations (in the same order as PFOS) were reported in liver of whales from the Canadian Arctic, from Iceland and the Faroe Islands and from Japan as well as in dolphins from Brazil (Table 1). It was reported that PFOSA concentrations in cetaceans were often higher than those of PFOS.…”
Section: Pfc Pattern In Marine Mammalsmentioning
confidence: 99%
See 2 more Smart Citations